A character driver of amplifier for the RF-generator 77.78 MHz at cyclotron DECY-13 in Yogyakarta - Atmono, Trimarji; Dwiatmaja, Agus; Piero, Muhamad Rangga Del; Suntoro, Achmad (Institute of Advanced Engineering and Science, 2024)
Measurement of power supply for design of experimental cyclotron in Yogyakarta (DECY-13), i.e. RF-generator 77.78 MHz, especially driver amplifier as important part, has been carried out, in order to minimize the reflected power. Starting from direct digital synthesizer (DDS) as exciter of the radio frequency (RF) wave, having power up to 20 W, the signal sent then to the driver, that has an amplifying factor of around 50. Output of driver works as input for final power of designed DECY-13, which needs about 10 kW of RF power supply for operating the cyclotron. Using network analyzer to get the best position of the RF-power-coupler, it was found the value of dee impedance equals to (50.9 - j0.3) Ω. The signal detected has the behavior as capacitively having value of around 6 nF, that showed by smith chart. An output of 0.8 W by DDS has resulted of 300W to the driver. By a pure resistance 50 Ω dummy load, the system can achieve final power of almost 10 kW.